Design and Analysis of Elektrical Appliance Experiment With Two Factorial Design (Jurnal Inovisi (Teknik Industri), 2006)
AbstractA rice cooker or rice steamer is a self-contained electrical appliance, used primarily for cooking. Here are also microwave, gas, and open flame variants. The preparation of rice has traditionally been a tricky cooking process that requires accurate timing, and errors can result in inedible undercooked or burnt rice. Rice cookers aim to avoid these problems by automatically controlling the heat and timing in the preparation of the rice, while at the same time freeing up a heating element on the range. In these experiments, we use three branch of rice cooker that is; A, B, and C. This entire product has capacity 1.8 liter. The load cook divided in three-load level; 0.5 liter, 1.0-liter end 1.5 liters. Each level or load cook has two times experiments. Time of experiments for each product is the same, with stopwatch, the speed of cooking can be able to identify. So each product can looked at how long spent the time for cooking the rice.Keywords: Design, Analysis,Electrical Appliance